The social life of kimono : Japanese fashion past and present - Cliffe, Sheila (Dress, body, culture., 2017)
"The kimono is an iconic garment with a history as rich and colourful as the textiles from which it is crafted. Deeply associated with Japanese culture both past and present, it has often been thought of as a highly gendered, rigidly traditional and unchanging national costume. This book challenges that perception, revealing the nuanced meanings and messages behind the kimono from the point of view of its wearers and producers, many of whom - both men and women - see the garment as a vehicle for self-expression. Taking a material culture approach, The Social Life of Kimono is the first study to combine the history of the kimono as a fashionable garment with an in-depth exploration of its multifaceted role today on both the street and the catwalk. Through case studies covering historical advertising campaigns, fashion magazines, interviews with contemporary kimono designers, large scale and small craft producers, and consumers who choose to wear them, The Social Life of Kimono gives a unique insight into making and meaning of this complex garment"--